2007
DOI: 10.1242/jeb.009779
|View full text |Cite
|
Sign up to set email alerts
|

Limits to sustained energy intake. X. Effects of fur removal on reproductive performance in laboratory mice

Abstract: . Manipulating metabolic parameters to improve growth rate and milk secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
133
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 131 publications
(151 citation statements)
references
References 93 publications
17
133
1
Order By: Relevance
“…We have previously repeated the shaving experiment of Król and colleagues (Król et al, 2007) on Swiss mice according to the same protocol with that performed on MF1 mice, and found that fur removal had an effect on food intake but although the effect on pup growth was in the expected direction it was not statistically significant (Zhao and Cao, 2009;Zhao et al, 2010a). These data were different from those observed in MF1 mice, and provided support for the peripheral limitation hypothesis.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…We have previously repeated the shaving experiment of Król and colleagues (Król et al, 2007) on Swiss mice according to the same protocol with that performed on MF1 mice, and found that fur removal had an effect on food intake but although the effect on pup growth was in the expected direction it was not statistically significant (Zhao and Cao, 2009;Zhao et al, 2010a). These data were different from those observed in MF1 mice, and provided support for the peripheral limitation hypothesis.…”
Section: Introductionmentioning
confidence: 77%
“…In contrast, when exposed to the hot conditions, the females had a reduced ability to dissipate heat, resulting in a lower food intake and less milk production . Consistent with this idea, dorsally shaved MF1 mice had increased thermal conductivity, and were thus able to produce more milk and wean heavier litters (Król et al, 2007). Studies on Brandt's voles (Wu et al, 2009) and Mongolian gerbils (Yang et al, 2013) both revealed that high temperatures (30°C) induced a reduction in milk production.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…the muscles or the mammary glands (Hammond et al, 1996;Zhao and Cao, 2009;Zhao et al, 2010). More recently, the 'heat dissipation limit theory' has been proposed, which suggests that animals may be limited by the capacity to dissipate heat generated as a by-product of processing food and producing milk (Król and Speakman, 2003a;Król et al, 2007;Speakman and Król, 2010;Speakman and Król, 2011). Although these experiments have greatly contributed to our understanding of the physiological mechanisms involved in imposing limits on SusEI, the individual variability in these limits has been largely ignored.…”
Section: Introductionmentioning
confidence: 99%
“…This may take place especially during late lactation, and failure to dissipate produced heat that might lead to hyperthermia, which has many negative effects on physiological functions [52]. Thus, heat dissipation limit can be considered as the key physiological mechanism linking current energy expenditure to life history in endothermic animals [40].…”
Section: Discussionmentioning
confidence: 99%